THE EFFECT OF BRILLIANT LEADERSHIP ON ENTREPRENEURIAL PERFORMANCE: AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT THE COLLEGE OF ARTS, TIKRIT UNIVERSITY (World Economics and Finance Bulletin, 2023)
The study aimed to identify brilliant leadership and its impact on entrepreneurial performance at Tikrit University, and to demonstrate the degree of brilliant leadership practices and the impact of its dimensions on entrepreneurial performance in the College of Arts, Tikrit University, and what is the importance of brilliant leadership and its impact on entrepreneurial performance in the College of Arts at Tikrit University. A questionnaire was used as a tool for the study, and the descriptive analytical method was used in the study, and to verify the research hypotheses, statistical methods were used, represented by correlation analysis and multiple linear regression analysis, and using the statistical program SPSS26, the data were analyzed The study sample consisted of (129) individuals working in the College of Arts, Tikrit University. The results of the study showed that the estimates of the study sample members about the effect of brilliant leadership on entrepreneurial performance were high, and the results of the study revealed that the dimensions of brilliant leadership (open leadership, closed leadership Taken together, they have a statistically significant impact on entrepreneurial performance at Tikrit University. The study also showed that the two areas of open leadership and closed leadership have the same strong correlation and influence on performance
Keywords: brilliant leadership; entrepreneurial performance.